Faktor Penentu Produksi pada Perkebunan Rakyat Kelapa Sawit di Kabupaten Mamuju Utara - Dimas deworo puruhito; Jamhari Jamhari; Slamet Hartono; Irham Irham (Universitas Gadjah Mada, 2019)
There are three patterns of smallholder oil palm plantation in North Mamuju regency, ie plasma, IGA (Income Generating Activity), and mandiri (independent). Independent smallholder plantations are plantations managed by the community themselves without the involvement of others. While the partnership patterns can be divided into plasma and IGA. The partnership is a form of fostering of smallholders plantations by large private plantation in this area. This study aims to determine the amount of oil palm production on smallholder plantations and the factors that affect.This research was conducted in North Mamuju Regency, West Sulawesi Province which has the widest smallholder oil palm plantation in Sulawesi Island with various pattern. Four villages in two sub-districts were chosen purposively consideration with having three patterns of smallholder plantations. Farmer samples were taken using the snowball method after stratification of the pattern was carried out. Data analysis was performed with Cobb-Doulas function model in the normalized logarithm, using Eviews 6 software. These findings are the average production of 56,840 kg, with productivity of 20,300 kg/ha. Input of land area, NPK fertilizer, age of oil palm crops, outside family labor, frequency of estate sanitation and distance of estate to river is the determinant input to production. Input land area is found as the most elastic input. However, land use for oil palm plantations should still refer to existing legislation